Bathyscidius mikati (Udržal, 1995), a new combination from the genus Bathyscia Schiødte, 1848 (Insecta, Coleoptera, Leiodidae, Cholevinae, Leptodirini) - Čeplík, Dávid; Lakota, Ján; Čeplík, Jaroslav (Zootaxa, 2021)
The study of the type material as well as the additional specimens collected in the Rumija Mts., southeastern Montenegro revealed that Bathyscia mikati Udržal, 1995 belongs to the genus Bathyscidius Jeannel, 1910. New combination, Bathyscidius mikati (Udržal, 1995) comb. nov. is established. The species redescription, morphological comparison with related species, revised distribution, the map and the catalogue for the genus are provided.